Regarding entrance of prototype room (PT2 toilet room on GF) materials supplied by client - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the entrance of prototype room (PT2 toilet room on GF) materials for BRACU new campus project.